Phylogenetic approach for identification and life cycles of Puccinia (Pucciniaceae) species on Poaceae from northeastern China - Ji, Jingxin; Li, Zhuang; Li, Yu; Kakishima, Makoto (Phytotaxa, 2022)
About 300 species of Puccinia on Poaceae have been reported globally. However, these species can be difficult to identify because of morphological similarities and difficulties of host plant identifications. The presence of many cryptic species is also suspected. Based on about 150 specimens on Poaceae and about 50 related specimens of spermogonial and aecial stages, all collected in northeastern China, a phylogenetic approach was conducted to clarify their identification and life cycles. In phylogenetic analyses 25 clades among specimens on Poaceae were detected. Each clade detected in phylogeny was interpreted as an independent species, although many clades were morphologically similar to each other. After comparative morphology with species previously reported, 17 species including three first records in China (P. cerienthes-agropyrina, P. coronati-agrostidis, P. coronati-hordei) were identified, and eight species (P. ampliaticoronata, P. digitaticoronata, P. eleganticoronata, P. elymi-albispora, P. oncospora, P. pileiformis, P. protuberanticoronata, P. ramificatacoronata) are described as new. In uredinial and telial stages, the host range of above 25 species was variable ranging from one host plant species to several host species, sometimes involving different grass genera. Thus, a phylogenetic approach is more suitable for species identifications of Puccinia on Poaceae rather than relying on rust morphology and host plant identification. Life cycle relations for 15 spermogonial and aecial species were also clarified by phylogenetic analyses. It is also suspected that grass rusts can be differentiated to species based on spermogonial and aecial stages on same or related host plants.